Soil properties (Sept 2020).xlsx - Gutierrez-Carazo, Encina (Cranfield University, 2022)
The excel described the main soil properties measured in the lab for quartz sand, sand and sandy loam soils.
Keywords: 'soil properties'; 'soil density'; 'soil columns'